CRITICAL ANALYSIS OF THE ORGANIZATION AND FUNCTIONING OF THE STATE PUBLIC SERVICE: CASE OF THE CONGOLESE NATIONAL POLICE - Joseph MWEZE SEBUMBA,; Pr Dr Christ Hermann POUNAH, (IJRDO - Journal of Social Science and Humanities Research, 2025)
The notion of the police is inherited from Antiquity with cities having retained a municipality. It is from the 9th century, in the « free towns » or free communes which have the right toadminister themselves. Under the old Regime, police power was exercised by municipal councils except in the capital, where, from the 8th century, it retuned to the city of Paris to be entrusted to an offficer of the king, called lieutenant-general of police. This notion which met with great institutional and doctinal success from the end of the 17th to the middle of the 18th century. We have long thoughtof « the police » essentially in their relationships to crime and norms and deviance, to order and disorder, to violence…But other essential questions require constant work and refined. A question arises that the existence of a National Police seems to have lost sight of :who owns the police powers ? We know that the answer is very different depending on the country, their history, their cultures and the times. If everything seems to oppose the Anglo-Saxon and French traditions was essentially multiple until 1941 and if, in the 19th Century, the central power had reserved the appointment of mayors, the latter became, by the Goblet law (1882) and the municipal law (1884) the real heads of the police («except in Paris, Lyon and a few cities whose police officers were state-controlled). They remained until 1941 and since 1978 we have seen the reappearance of munocopal police forces.Furthermore, in the Democratic Republic of Congo, police powers belong to the State and come under the Ministry of the Interior.